Pelatihan Model-Model Pembelajaran Anak Usia Dini di Pos PAUD Kecamatan Delanggu, Kabupaten Klaten - Ummi Hany Eprilia; Surtikanti Surtikanti; Aryati Prasetyarini (Universitas Muhammadiyah Surakarta, 2010)
The training for kindergarten teachers was conducted to equip them with knowlegde on the models of teaching to young learners. In general, the training involves the concept of teaching model, atractive model and its implementation, basic concept of teaching mathematics, reading and writing, and children cognitive development. After training, set of questionaire was distributed to see whether they master the knowledge given or not and to identify the teachers’ needs to determine the next topic. Based on the questionaire, it was found that they need to learn classroom management, curriculum, and teaching methods. Since most of the participants (80%) were housewives who did not have background knowledge on teaching young leaners, it was difficult enough to explain the knowledge. However, the participants confessed that they get knowlegde on how to teach young learners.